Extraction of Flavonoid from Rice Straw: The Study of Total Phenolic Content (TPC), Total Flavonoid Content (TFC) and Antibacterial Activity - Lestari, Siti; Sunaryo, Tri; Arvianto, Rizky Ibnufaatih (Malaysian Journal of Science (MJS), 2025)
The combustion of rice straw results in air pollution and a decrease in soil fertility. This research aims to extract flavonoids from rice straw and evaluate their antibacterial properties. The extraction of flavonoids from rice straw was conducted using Soxhlet, reflux, and maceration methods. These extraction techniques were subsequently compared based on the Total Phenolic Content (TPC) and Total Flavonoid Content (TFC). The optimal extraction method for rice straw involved ethanol solvents with concentrations of 0%, 25%, 70%, and 96%. This same optimal method was used to extract rice straw at various time intervals, specifically 12 hours, one day, and three days. A comparative analysis of ethanol concentration and extraction duration was performed based on the Total Phenolic Content (TPC) and Total Flavonoid Content (TFC). The rice straw extract underwent the disc diffusion method for antibacterial tests against gram-positive (Staphylococcus aureus) and gram-negative (Escherichia coli) bacteria. The antibacterial efficacy of rice straw extract was evaluated based on its ability to inhibit the growth of these microorganisms. The maceration method proved to be the most effective for extracting rice straw due to its significantly greater total flavonoid content (TFC) value compared to the reflux and Soxhlet extraction methods. Increasing the ethanol concentration from 0% to 96% and extending the extraction time from 12 hours to 3 days led to a proportional increase in total phenolic content (TPC) and TFC. Ethanol at a concentration of 96% was the most appropriate solvent for extracting rice straw due to its highest total flavonoid content (TFC) value relative to other ethanol concentrations. A three-day extraction period was optimal, yielding a significantly higher TFC value than 12-hour and one-day extractions. Furthermore, it is noteworthy that rice straw extract exhibits greater inhibition of gram-negative bacteria (Escherichia coli) than gram-positive bacteria (Staphylococcus aureus). The antibacterial activity of rice straw extract correlated with the flavonoid content in the sample.